Explaining Chinese Delinquency: Self-Control, Morality, and Criminogenic Exposure - Wu, Yuning (Criminal justice and behavior, 2022)
This study extends the testing of situational action theory (SAT) to a Chinese population, and sheds new light on the directions of the moderation relationships between self-control and morality, and between crime propensity and criminogenic exposure on delinquency. Relying on a large, representative sample of middle school students from two areas of Guizhou, China (N = 2,498), we find that both self-control and morality have significant inhibiting effects on delinquency. Moreover, self-control has a more profound curbing effect on delinquency among adolescents with higher levels of morality. Meanwhile, the promoting effect of crime propensity on delinquency decreases when levels of risky exposure increase. When adolescents have more unsupervised activities and delinquent peers, their crime propensity affects delinquency to a lesser extent. Our study confirms that individual and situational factors interlock in determining delinquency, and reiterates the value of empirical testing across cultures to validate and possibly improve general theories of crime.